Development of silicon strip detectors with orthogonal field - Saymbetov, A.K.; Imanbayeva, A.K.; Toshmurodov, Y.K.; Mukhametkali, B.K.; Japashov, N.M.; Ayazbay, Zh.G. (Recent Contributions to Physics, 2017)
The development of semiconductor strip detectors with orthogonal field with high energy and position resolution, linearity of the signal over a wide energy range for various types of particles, is closely linked with the technology of manufacturing the detection modules and semiconductor properties of the original crystal. In this paper we consider the physical and technological features of manufacturing of Si (Li) strip detectors with orthogonal field with a large sensitive area. The manufactured detectors have following electro-physical and radiometric characteristics: under working voltage U = (50-600)V shows the I ~ (0,1÷0,5) µА reversed current, capacitance is С = 25 pF, noise E = (12÷35) keV, energy resolution Rβ = 18 keV from the source of 207Bi (Eβ = 1МeV) and Rα = 46 keV from the source of 238Pu (Eα ≈ 5,5MeV). Investigation of the impact of irregularities on characteristics of strip detectors, as well as their role in the phenomena of charge transport in a condition of orthogonal field.